Electronic characterization of silicon intercalated chevron graphene nanoribbons on Au(111) - Deniz, Okan; Sanchez-Sanchez, C.; Jaafar, R.; Kharche, N.; Liang, Liangbo; Meunier, Vincent; Feng, Xinliang; Muellen, K.; Fasel, Roman; Ruffieux, Pascal (Chemical Communications, 2018)
Electronic and thermal properties of chevron-type graphene nanoribbons can be widely tuned, making them interesting candidates for electronic and thermoelectric applications. Here, we use post-growth silicon intercalation to unambiguously access nanoribbons' energy position of their electronic frontier states. These are otherwise obscured by substrate effects when investigated directly on the growth substrate. In agreement with first-principles calculations we find a band gap of 2.4 eV.
CRIS-Team Scopus Importer:2023-03-20